RISET MAHASISWA KONSTRIBUSI KEKUATAN LENGAN DAN KESEIMBANGAN TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI PADA SISWA EKSTRAKURIKULER SMPN 6 PALOPO - Rahmat, Dede; Nur, Suaib; A. Heri Riswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the contribution of arm muscle strength and balance to the under-passing ability of volleyball extracurricular students at SMPN 6 Palopo. Using a quantitative correlational approach with a total sample of 32 students, data were collected through a push-up test to assess arm muscle strength, a modified Bass Balance Test to measure balance, and an under-passing test to evaluate technical performance. Descriptive analysis indicated that students’ physical and technical abilities were in the moderate to good category, and normality tests confirmed that all data were normally distributed. The results of the regression analysis showed that arm muscle strength contributed significantly to under-passing ability with a determination coefficient of 94.5%, balance contributed 42.7%, and both variables simultaneously contributed 93.9%. These findings highlight the substantial role of physical components—particularly arm strength and balance—in enhancing under-passing skills. Therefore, coaches and physical education teachers are encouraged to include strength and balance training components in their volleyball training programs to improve students' performance.